The Role of Strategic Leadership in Adopting Sustainable Marketing Strategies: An Analytical Study of the Opinions of Administrative Leaders in a Number of Private Banks (Erbil and Sulaymaniyah Banks as a Model) - Arif Saeed Hawary, Kadhim Faraj; Salar Majeed, Shilan (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
This research aims to identify the role of strategic leadership in the adoption of sustainable marketing strategies in private commercial banks. The research was conducted on two main aspects, the first being as a descriptive document, consisting of several kinds of literature to illustrate the theoretical background of both strategic leadership and sustainable marketing strategies presented by writers and researchers in their scientific products. The second method is analytical exploratory, through an analytical study in the light of the preparation of a questionnaire prepared for collecting data and information on the study. The researchers tried to ask several questions expressing the problem of the study, which was the basis of the research curriculum and its reliance on it in the field. The main question was: Does strategic leadership play a role in adopting sustainable marketing strategies in the banks in question? To answer this question, a hypothetical research chart reflecting the relationships and influences between the study’s variables was drafted, resulting in a series of main and sub-hypotheses tested using a nuseveraltistical means of data collected in identification and dist.distribution80) Form on Directors of Banks and Division Officials represented by (Director of Bank, Assistant Director, Division Officer (Current and Saving), Credit Officer, Securities Section, Remittances Section, Management and Self-Management, Safe (Fund) ". It was (140) a valid form for analysis, the data collected were analyzed based on statistical, descriptive methods according to the statistical package (Spssv.21). The study reached a set of conclusions, the most important of which was the existence of a correlation and impact between strategic leadership and sustainable marketing strategies, with this relationship varying at the sub-dimensional level in the light of the responses of the research individuals, which underscores the importance of strategic leadership in adopting the sustainable marketing strategies of the research banks. Building on the conclusions of the research, both theoretical and field-based, suggestions were made in line with these conclusions, the most important of which is the need to apply sustainable marketing strategies in researching banks and adapt their dimensions to their reality because they are modern marketing strategies that seek sustainability in their marketing activities and sustain the relationship with the customer and the well-being of society. I conclude the research with a series of proposals and future studies.